New saber-toothed cat records (Felidae: Machairodontinae) for the Pleistocene of Venezuela, and the Great American Biotic Interchange - Rincón, Ascanio D. (2011)
The Machairodontinae fossil record in South America is not very diverse. Until now, only the genus Smilodon (Smilodontini) has been reported, with likely a single species, S. populator. A second taxon of Machairodontinae was referred to Homotheriini and to the genus Xenosmilus, but the age to which it was assigned, early to middle Pleistocene, is uncertain, because it was recovered out of stratigraphic context. At present, the Venezuelan saber-toothed cat record is limited to the late Pleistocene, and consists of fossils found in Mene de Inciarte (state of Zulia), and from Zumbador cave deposit in the state of Falcon. Here we report a new species of Machairodontinae Homotherium venezuelensis, nov. sp., as well as the first record of Smilodon gracilis in South America. Both were found in El Breal de Orocual, a tar seep in the state of Monagas, northeastern Venezuela. The age of the deposit has been interpreted as early to middle Pleistocene by thermoluminescence dating. We have been able to identify 30 vertebrate taxa, suggesting a paleoenvironment similar to the Venezuelan llanos today: an extensive savanna with rivers and patches of gallery forest. The saber-toothed cats described here demonstrate that the biogeography of Neotropical felids is more complex than previously thought, and allow us to identify new invasions and delimit the times during which they occurred. The fossils from Orocual represent the first record of Homotherium for South America, indicating that scimitar-toothed cats invaded this continent as early as the early-middle Pleistocene.